The impacts of child marriages on young girls: case study of Mutasa district - Mutandwa, Adolf Tinashe (Midlands State University, 2018)
Despite international agreements and national laws, marriage of girls below 18 years of age is common worldwide and affects millions. Child marriage, defined as marriage of a child below 18 years of age is an ancient worldwide custom. Other terms applied to child marriage include "early marriage" and "child brides." Child marriage is a human rights violation that prevents girls from obtaining an education, enjoying optimal health, bonding with others their own age, maturing, and ultimately choosing their own life partners. Child marriage is driven by poverty, religious beliefs, security of the child to mentions just a few. This thesis therefore seeks to depict the drivers of child marriages in Mutasa pointing out also the effects on girls' health: increased risk for sexually transmitted diseases, death during childbirth, and obstetric fistulas, school dropout, domestic violence, child sexual abuse and poverty. Critical issues are the high prevalence of HIV/AIDS among young people; childbearing by young girls, which can lead to obstetric fistulas and death of the mother; and child marriage Girls' offspring are at increased risk for premature birth and death as neonates, infants, or children. To stop child marriage, this study points out possible strategies or policies and programs that must be implemented like educate communities, raise awareness through NGOs and relevant line government ministries, engage local and religious leaders, involve parents, and empower girls through education and employment. Awareness of reproductive health issues in most affected areas in developing nations is of paramount importance to combat the problem of child marriages.